Problems of development of Islamic finance in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
The global economic crisis has shown how viable Islamic finance. One of the biggest advantages of Islamic finance is that the interest rate will be charged. Bank interest is incompatible with Sharia law. Islamic banking in-volves the financing through the participation of an investor in the share cap-ital. This income is composed by issuing special securities and the income from them is invested in the real sector of the economy. The most attractive aspect of this model is the spiritual purity of the business. In Islamic banking financing can get many promising projects, even in the absence of collateral. However, before giving the loan, the project is carefully analyzed: how eco-nomically viable it is, what are the prospects of development of situation in this market segment, studied business as a client.A good investor can give a lot more and a lot of it may adopt. It comes and businessmen around the world. In this regard, the role of Islamic fi-nance in recent years has increased worldwide, and including us.
Keywords: Islamic financing; principles of Shariat; Islamic banking; financial products; Islamic financial assets.